The Influence of EFL Students’ Self-Confidence and Motivation on Speaking Performance - Fitrah, Atiyah Inayah; Korompot, Chairil Anwar; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2025)
This research aims to examine the influence of EFL students’ self-confidence and motivation on speaking performance. A quantitative approach with an ex post facto design was employed. The research population consisted of English Language Education students from Universitas Negeri Makassar, batch 2022, and cluster random sampling was used to select twenty-eight respondents. Data collection was carried out using questionnaires and a speaking test. The data were analyzed using f-test statistic with a significant value of 0.05. The results of the data analysis revealed that the sig. value of f-test is .000 < 0.05, therefore the H1 is accepted, where there is a significant influence between self-confidence and motivation on speaking performance, and H0 is rejected. As a result, the research findings suggest several implications. Firstly, highlight the need for fostering a supportive and encouraging classroom environment. Secondly, incorporating students’ interests and real-life scenarios into the curriculum can increase their motivation. Thirdly, the research suggests that integrating activities that build both self-confidence and motivation into the EFL curriculum can lead to significant improvements in speaking performance.